An Efforts Increasing the Student Learning Concentration Using a Group Tutoring Approach Self-Management Techniques - Nurjanah, Siti; Prayogi, Fiki; Sutrisno, Joko (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research is motivated by some students who have not been able to concentrate in learning, so that efforts are needed to improve student learning concentration by using the right techniques. The purpose of this study was to determine the effectiveness of efforts to improve student learning concentration using Self-management techniques through group guidance in class XI IPA 1 SMA Tamansiswa Teluk Betung in the 2022/2023 academic year